CdxHg(1−x)Te Alloy Colloidal Quantum Dots: Tuning Optical Properties from the Visible to Near‐Infrared by Ion Exchange. (18th February 2013) - Gupta, Shuchi; Zhovtiuk, Olga; Vaneski, Aleksandar; Lin, Yan‐Cheng; Chou, Wu‐Ching; Kershaw, Stephen V.; Rogach, Andrey L.
<x xml:space="preserve">Abstract</x> The energy gap between valence and conduction levels in colloidal semiconductor quantum dots can be tuned via the nanoparticle diameter when this is comparable to or less than the Bohr radius. In materials such as cadmium mercury telluride, which readily forms a single phase ternary alloy, this quantum confinement tuning can also be augmented by compositional tuning, which brings a further degree of freedom in the bandgap engineering. Here it is shown that compositional control of 2.3 nm diameter CdxHg(1−x)Te nanocrystals by exchange of Hg2+ in place of Cd2+ ions can be used to tune their optical properties across a technologically useful range, from 500 nm to almost 1200 nm. Data on composition‐dependent changes in the optical properties are provided, including bandgap, extinction coefficient, emission energy and spectral shape, Stokes shift, quantum efficiency, and radiative lifetimes as the exchange process occurs, which are highly relevant for those seeking to use these technologically important QD materials.